A Geometallurgical Approach of the Copper-Nickel-Platinum Group Elements Maturi Deposit, Minnesota, USA, Using Quantitative Mineralogy - Nicole Hoffmann; Charles Knilans; Tassos Grammatikopoulos (Canadian Institute of Mining, Metallurgy and Petroleum, 2015)
"Twin Metals Minnesota LLC, (TMM) has recently completed a prefeasibility study evaluating the development and operation of an underground copper (Cu), nickel (Ni), platinum (Pt), palladium (Pd), and gold (Au) mining project on the Maturi deposit in northeastern Minnesota.The Maturi deposit is a magmatic Cu-Ni-sulphide deposit occurring along the basal contact of the South Kawishiwi intrusion, comprised of heterogeneous troctolites to gabbros forming a tabular body designated the BMZ (basal mineralized zone). These rocks provide the major gangue mineralogy (plagioclase, olivine, and clinopyroxene) with local, minor rock-forming orthopyroxene, biotite, magnetite, and ilmenite. Altered silicates exist within local fracture and/or alteration zones, which are commonly associated with minor faults in the regional area. The Maturi deposit is comprised of four main mineralized zones within the BMZ, referred to as Stage 1, Stage 2 (S2), Stage 3 (S3), and Upper Heterogeneous. Chalcopyrite, cubanite, pentlandite, and pyrrhotite are mainly hosted within the S2 and S3 units, with talnakhite frequently occurring within the S3 unit.A cross-discipline approach combining geology, geochemistry, metallurgy, QEMSCAN™ mineralogy, and mine planning has been implemented to develop a preliminary geometallurgical model and life of mine metallurgical performance forecast. This paper provides an overview of the methods that were used to develop the model and forecast, and discusses the advantages of such a model in project development and evaluation.INTRODUCTIONThe TMM Project proposes mining a copper-nickel-palladium-platinum-gold-silver (Cu-Ni-PGM) magmatic sulphide deposit situated in the Duluth Complex of northeastern Minnesota, USA. The prefeasibility study proposes a 45,000 million tonnes per day mine and concentrator facility to produce two saleable concentrates. The mine will access two separate deposits, Maturi and Maturi Southwest. Saleable concentrates are the final products of the sequential flotation plant where a high grade Cu concentrate is produced followed by a Ni concentrate."